2016
DOI: 10.5958/0975-6906.2016.00022.5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association and frequency distribution in segregating generations derived from pigeonpea crosses

Abstract: Correlation and presence of genetic interactions was studied using F 2 and F 3 generations in three pigeonpea crosses for yield and its component traits. Most of the characters studied were positively skewed and were being governed by several genes indicating quantitative inheritance. Variance, skewness and kurtosis have also indicated that homozygosity has increased over the generation in pigeonpea crosses. Cross BRG 1 x ICP 8863 was found better than other two crosses (TTB 7 x ICP 8863 and TTB 7 x ICPL 87119… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…These results are in agreement with those of Prabhu et al (2015). Ajay et al (2016) observed duplicate interactions for plant height, whereas pod yield per plant had complementary gene interaction in some crosses and duplicate gene interaction in other crosses of pigeon pea.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…These results are in agreement with those of Prabhu et al (2015). Ajay et al (2016) observed duplicate interactions for plant height, whereas pod yield per plant had complementary gene interaction in some crosses and duplicate gene interaction in other crosses of pigeon pea.…”
Section: Resultsmentioning
confidence: 88%
“…Byadagi et al (2018) observed a large shift in trait mean values from F 2 to F 3 generation for all traits in the three peanut crosses. This kind of shift in correlation coefficients between generations was attributed to the difference in gene complementation of linkage blocks and is an indication of the unstable nature of the breeding population (Ajay et al 2016). It was concluded that yield contributing traits such as the number of branches per plant, pod yield per plant, and the number of pods per plant are governed by complementary gene action in both crosses.…”
Section: Character Associationmentioning
confidence: 99%
“…The frequency distribution for texture was continuous in the population meaning the trait was quantitatively controlled. Some progenies had pulp texture similar to or higher than that of the parents indicating positive transgrassive segregation with positive skewness (Figure 1D), thus complementary gene action (Ajay et al, 2016). The transgressive segregation was an indication of complementally gene action between the parents, positive skewness indicated predominance of additive gene action and desirable alleles could be fixed in early generations (Roy, 2000).…”
Section: Physio-chemical Variability In Crossesmentioning
confidence: 98%
“…The crop's genetic diversity serves as a valuable resource for breeders aiming to enhance traits such as yield, resistance to diseases, and tolerance to environmental stressors. The identification of transgressive segregants, individuals displaying traits that surpass those of their parental lines, holds great promise for accelerating the breeding process and unlocking novel genetic combinations [4,5].…”
Section: Introductionmentioning
confidence: 99%